Hak Pegawai Negeri Sipil dan Pegawai Pemerintah dengan Perjanjian Kerja Menurut Undang-Undang Nomor 20 Tahun 2023 Tentang Aparatur Sipil Negara, Ditinjau dari Segi Keadilan - Emanuel De Jesus; Yohanes G.Tuba Helan; Norani Asnawi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The State Civil Apparatus or commonly referred to as ASN has been in the spotlight lately, where the changes in the new laws and regulations greatly affect the two (2) management of ASN, which includes Civil Servants (PNS) and Employees Government with Work Agreement (PPPK). This study aims to find, examine and discuss in more detail related to the Amendment of Law Number 20 of 2023 concerning Civil Servants, more specifically related to the Rights of Civil Servants and PPPK which have been regulated in this Law. The research method used is the cutative descriptive method. This type of research is normative legal research, the source of data obtained by researchers is sourced from legal materials, journals, and literature that supports this research. The legal materials used are primary, secondary and tertiary legal materials, while the literature includes contemporary and classical books. Data obtained by researchers through legal materials, then read, examined, analyzed, and explained quantitatively using scientific logic. The results showed that the granting of rights to Civil Servants and Government Employees with Work Agreements, was in accordance with their respective positions in the field of employment. However, the rights of the two management are dynamic and uncertain, because they are very dependent on changes in the laws and regulations ratified, so that there is a need for permanent regulations related to the rights of the two management, in order to fulfill the rights of each employee, which is in accordance with the Laws and Regulations.